Review of Fund Facilities-Analytical Basis for Fund Lending and Reform Options. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
In the context of the ongoing review of Fund facilities, this paper examines the analytical basis for Fund lending in emerging market countries and provides a broad-ranging perspective for reforming the General Resources Account (GRA) lending toolkit. The Fund's important lending role in crisis prevention and resolution is buttressed by its unique characteristics: (i) its ability as a nonatomistic lender to provide large-scale financing and reduce the likelihood of a run by private creditors; (ii) its ability as a cooperative institution with near-universal membership to agree conditionality with members, thus providing national authorities with a policy commitment tool to underpin confidence and catalyze private lending; and (iii) its de facto preferred creditor status, which allows it to provide crisis financing when private creditors may be reluctant to lend.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet